Flores Florentino : Dead Sea Scrolls and other early Jewish studies in honour of Florentino Garcia Martinez - García Martínez, Florentino.; Hilhorst, A.; Puech, Emile.; Tigchelaar, Eibert J. C. (Supplements to the Journal for the Study of Judaism, 2007)
This volume contains forty-eight essays, presented by friends, colleagues and students from many countries, in honour of Florentino García Martínez, director of the Groningen Qumran Institute, editor-in-chief of the Journal for the Study of Judaism, and professor in Leuven. The majority of the essays are in the areas of the honoree's own scholarship and interests, including primarily Qumranica, but also many other fields of Second Temple Judaism, from late biblical texts and Septuagint up to early rabbinic writings. Florentino's own polyglottism, evident from his bibliography, and his close relations with many scholars from Southern Europe, is reflected in the inclusion of a few French, Spanish and Italian articles in this volume.